Polydopamine‐functionalized monolithic silica column for mixed‐mode chromatography†. Issue 9 (10th May 2013) - Zhou, Qiaoli; Yang, Peiling; Xiao, Xing; Jia, Li
<x xml:space="preserve">Abstract</x> Dopamine is easy to self‐polymerize under alkaline conditions and the resultant polydopamine is easy to adhere to the surface of many organic and inorganic materials. Based on the characteristics of dopamine, in this paper, a new polydopamine functionalized monolithic silica column was successfully prepared for performing mixed‐mode chromatography. The performance of the column was evaluated by the separation of different types of samples including alkylbenzenes, polycyclic aromatic hydrocarbons, aromatic acids, phenols, and bases. The mechanism for the separation of these compounds was studied and appeared to involve the mixed interactions containing π‒π, hydrophobic, electrostatic, and hydrophilic interactions.